التخطيط الاستراتيجي التسويقي وأثره في جودة الخدمة لمصرفية : دراسة استطلاعية في فروع مصرفي الرافدين و الرشيد في مدينة الموصل - د. نجلة يونس محمد ال مراد; ثائر طارق حامد الملا حسن (PROSPECTIVE RESEARCHES, 2023)
The study deals with the subject of marketing strategic planning and its effect on the quality of banking service. The problem is reflected by the lack of dealings by people of different classes in dealing with bank, and the decrease of the size of performances and activities practiced by banks facilities connected with commerce and investment. The study puts a primary hypothesis which indicates that all the obstacles are the result of banks not following the strategic approaches concerning the service of marketing planning in order to insure the offer of services which meet the need of customers and their desires. Data, and collected from employees working at banks and clients. This data has been analyzed using Dunkin analysis and simple and multiple regression factors. As a result, it is found that there are abstract differences between the variables of marketing strategic planning and the variables of the quality of bank services. Also there is an abstract effect of independent variables which are represented by strategic planning in the dependable variables which are represented by the quality of banking service.